Effectiveness of Marketing Mix Strategies on Customer Satisfaction, Loyalty and Retention in Banking: Case Study of Zenith Bank Plc, Nigeria - Asekome , Elma (Archives of Business Research, 2020)
The objective of this study was to ascertain the effectiveness of Zenith Bank marketing mix strategies on customer satisfaction, loyalty and retention and how to improve on them. Data were collected from primary sources through a questionnaire made up of descriptive options in a 5- scale Likert research format. The data were subjected to empirical analysis using the SPSS software to estimate the mean distribution, standard deviation, Pearson’s correlation coefficient, analysis of variance (ANOVA) as well as multiple regression analysis to test the set hypotheses. The result of the analysis revealed that though each of the elements of the marketing mix strategies influences the effectiveness of Zenith Bank marketing, product, process and personnel were more significant in contributing to meeting customer satisfaction, customer loyalty and customer retention. The study recommended the need for the Bank to continue to improve on these significant strategies as well as improving on other strategies that could attract, meet and exceed customer expectations such as enhancing transaction process flow, continuous training of the Bank personnel and providing the latest technological innovations to ensure error free transactions. The study further recommended the need to increase the Bank corporate social responsibility by sponsorship of social events that could increase its marketing visibility as well as avoiding incidences of cash shortage at ATM points to reduce customer complaints.